Empowering Indonesian migrant workers through financial literacy and investment education - Saputri, Agatha; Adhi Nugroho, Mahendra; Zylio Nugraha, Andro (Universitas Negeri Yogyakarta, 2025)
Indonesian Migrant Workers (PMI) contribute significantly to the national economy, with remittances exceeding USD 10 billion annually. These funds not only support household incomes but also enhance the country’s balance of payments. However, many PMI lack sufficient financial literacy, leading to poor financial planning, impulsive spending, and vulnerability to financial fraud, particularly illegal investment schemes. To address these challenges, this community service program was implemented to improve financial literacy and investment capacity among PMI in Malaysia. The program applied a participatory, community-based approach and was delivered over four weeks in eight interactive sessions using blended learning methods. Training content was tailored to the socio-cultural realities of PMI, covering essential topics such as budgeting, saving, debt management, legal investments, and the use of financial technology (fintech). Quantitative evaluation through pre- and post-tests indicated a substantial improvement in financial knowledge, with average participant scores increasing by 64.8%. Over 80% of participants successfully developed personal and household financial plans, while 70% demonstrated the ability to differentiate between legal and illegal investments. Qualitative insights from interviews and reflective journals revealed behavioral changes, such as reduced impulsive spending, increased savings discipline, and stronger motivation for financial independence. Significantly, several participants committed to becoming community financial literacy ambassadors, demonstrating the program’s potential for sustainable impact beyond the training sessions. These findings highlight that a contextually adapted, community-driven educational model can effectively empower PMI to make informed financial decisions, enhance their economic resilience abroad, and support a smoother financial reintegration upon returning to Indonesia.